2009
DOI: 10.1159/000243786
|View full text |Cite
|
Sign up to set email alerts
|

Sarcoidosis-Associated Fibrosing Mediastinitis with Resultant Pulmonary Hypertension: A Case Report and Review of the Literature

Abstract: Pulmonary hypertension, a common manifestation of advanced sarcoidosis, is thought to result from fibrosis with chronic hypoxia and destruction of small vessels, extrinsic compression of pulmonary arteries, or granulomatous vasculitis. We report a case of sarcoidosis-associated pulmonary hypertension due to fibrosing mediastinitis. Our patient presented with cough and dyspnea on exertion and was found to have pulmonary artery enlargement, pulmonary venous compression, and mediastinal soft tissue enhancement on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 46 publications
1
28
0
5
Order By: Relevance
“…In situ thrombosis (thrombotic angiopathy) is another intravascular mechanism, which has been described previously [13]. More proximally, mediastinal or hilar adenopathy and any accompanying fibrosis can result in mechanical extrinsic compression of the large pulmonary arteries and an increased pulmonary vascular resistance (figs 1 and 4) [11,[17][18][19].…”
Section: Pathophysiology Of Ph In Sarcoidosismentioning
confidence: 99%
“…In situ thrombosis (thrombotic angiopathy) is another intravascular mechanism, which has been described previously [13]. More proximally, mediastinal or hilar adenopathy and any accompanying fibrosis can result in mechanical extrinsic compression of the large pulmonary arteries and an increased pulmonary vascular resistance (figs 1 and 4) [11,[17][18][19].…”
Section: Pathophysiology Of Ph In Sarcoidosismentioning
confidence: 99%
“…Pulmonary vein involvement by fibrosing mediastinitis has also been reported in sarcoidosis. Yangui et al reported a case of sarcoidosis with pulmonary vein stenosis and pulmonary edema secondary to fibrosing mediastinitis (7), while Toonkel et al also noted a case of pulmonary vein obstruction due to fibrosing mediastinitis that led to PH in a sarcoidosis patient (8).…”
Section: Figure 7 Chest X-ray and Ct Findings At 6 Months After Begimentioning
confidence: 99%
“…Systemic corticosteroid administration has been reported to be effective to relieve the symptoms in 2 cases (7,8), which were also associated with a regression of mediastinal soft tissue and reduced pulmonary arterial pressures. On the other hand, corticosteroid treatment did not normalize the narrowed major vessels in all cases.…”
Section: Figure 7 Chest X-ray and Ct Findings At 6 Months After Begimentioning
confidence: 99%
“…This suggests that age-related changes in females, such as the hormonal dysregulation associated with menopause, may contribute to sarcoidosis. Although significant heterogeneity in disease presentation and disease severity occurs among different ethnic and racial groups [13,14,15,16], both of these pulmonary granulomatous diseases, sarcoidosis and nontuberculous mycobacterial disease, are likely to be characterized by a preponderance in postmenopausal females. Therefore, it is likely that fluctuations of sex hormones may be associated with enhanced granuloma formation in the lung.…”
Section: Introductionmentioning
confidence: 99%